Antileishmanial activity evaluation of bis-lawsone analogs and DNA topoisomerase-I inhibition studies. (April 2014) - Sharma, Garima; Chowdhury, Sayan; Sinha, Suman; Majumder, Hemanta K.; Kumar, S. Vasanth
Abstract For the development of potent novel antileishmanial agents, 3, 3′-(arylmethylene)bis(2-hydroxynaphthalene-1, 4 dione) derivatives were synthesized from lawsone and evaluated for cytotoxicity on Leishmania donovani promastigotes as well as on leishmanial DNA topoisomerase-I. Enzyme inhibition studies were conducted with simultaneous and preincubation conditions. Total inhibition is compared to camptothecin (CPT), which was taken as positive control on both the systems of enzyme inhibition. The range of activity varied from 37.5 to 70 µM in simultaneous assay and 13–16 µM in preincubation assay. Furthermore, when evaluated against L. donovani promastigotes, the synthesized compounds exhibited the activity ranging from 2 to 14 µM. The results revealed that all the compounds exhibit promising antileishmanial activity.